2022
DOI: 10.1007/s11249-022-01624-0
|View full text |Cite
|
Sign up to set email alerts
|

The Tribocorrosion Behaviour of Ti-6Al-4 V Alloy: The Role of Both Normal Force and Electrochemical Potential

Abstract: The tribocorrosion behaviour of Ti-6Al-4 V exposed to phosphate buffered saline was investigated under a range of normal forces in both cathodic and anodic regions to provide a basis for properly deriving the tribological constants of this alloy. To achieve this, a new customised tribotester was designed and manufactured to rub the Ti-6Al-4 V disks against zirconia balls. The tests were conducted at a sliding frequency of 1 Hz and a sliding distance of 4.8 mm under various normal forces and potentials as 17.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…The basic data for such a modeling procedure can be obtained by fundamental tribocorrosion studies in the ball-on-disc configuration. The role of mechanical and electrochemical reactions in the total tribocorrosion loss changes with various parameters such as the imposed potential [ 48 , 49 ], normal force (and, thus, contact pressure) [ 50 , 51 ], sliding distance and its frequency [ 52 , 53 , 54 ], material couple in contact [ 55 , 56 , 57 , 58 ], and the solution type and its acidity [ 59 , 60 , 61 ]. However, the design parameters of head–neck junctions including taper angle mismatch, head size, trunnion geometry, material couples in contact, and the solution acidity, together with the presence of proteins, could affect the tribological characteristics of the system, the governing potential, and the degree of mechanical and electrochemical damage processes.…”
Section: Discussionmentioning
confidence: 99%
“…The basic data for such a modeling procedure can be obtained by fundamental tribocorrosion studies in the ball-on-disc configuration. The role of mechanical and electrochemical reactions in the total tribocorrosion loss changes with various parameters such as the imposed potential [ 48 , 49 ], normal force (and, thus, contact pressure) [ 50 , 51 ], sliding distance and its frequency [ 52 , 53 , 54 ], material couple in contact [ 55 , 56 , 57 , 58 ], and the solution type and its acidity [ 59 , 60 , 61 ]. However, the design parameters of head–neck junctions including taper angle mismatch, head size, trunnion geometry, material couples in contact, and the solution acidity, together with the presence of proteins, could affect the tribological characteristics of the system, the governing potential, and the degree of mechanical and electrochemical damage processes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the important role played by the normal force on mechanical wear accelerated corrosion, and fluid lubrication in the tribocorrosion of passive metals. 16,17,27,31 Figure 3 shows the effect of normal force on the mechanical, chemical, and total wear rates of tungsten in tribocorrosion according to the model. Both of the mechanical and chemical wear rates increase at higher normal force, while it is interesting to see that the mechanical and chemical wear curves intersect at the normal force of approximately 60 N. Specifically, the effect of normal force on the chemical wear rate is less and less pronounced with the increase of the normal force while the effect of normal force on the mechanical wear rate keeps enhancing at higher normal force.…”
Section: Effect Of Normal Forcementioning
confidence: 99%
“…the clear dependence of anodic current on the applied potential which is consistent with the observations found in the tribocorrosion of other passive metals. 16,17,25 However, a reliable model to predict the influence of these parameters on the material removal of tungsten in tribocorrosion is not yet developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further improve the estimation of the material loss during the operation of the hip implant, the tribocorrosion (fretting corrosion) phenomenon at the head-neck junction requires investigation. To achieve this, both the mechanical wear and electrochemical corrosion need to be modelled simultaneously [ 17 ]. Modelling tribocorrosion has been a major challenge for researchers, due to its complexity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%